Development of New Todame Learning Media to Improve Problem-Solving Skills on Newton's Law for High School Students - Ghinatri, Nurma; Ika Mustika Sari; Duden Saepuzaman (Department of Physics Education, Universitas Mataram, 2024)
The problem-solving skills of Indonesian students are still relatively low, especially in complex subjects like Newton's law in Physics. Therefore, a learning Media is needed to improve these skills, such as the Tournament-based Truth or Dare Online Card (New Todame) to enhance problem-solving abilities, specifically on Newton's law. This study aims to: (1) gather information about media needs from teachers and students, (2) develop New Todame media, (3) assess the feasibility of the media, (4) gather feedback on user satisfaction, and (5) examine the improvement in problem-solving skills after using the New Todame media. This research is development research (R&D) using the ADDIE design, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. Data collection was done through interviews, preliminary study questionnaires, validation sheets, feasibility questionnaires, and pretest & posttest sheets. The results indicate that New Todame is feasible for use, and there is an improvement in problem-solving skills on Newton's law after using the New Todame media, with an N-Gain score of 0.455, categorized as moderate.